Adventist education and its reason for being - Mendoza Orbegoso, Oscar (2016)
The biblical apocalyptic vision has given the Seventh-day Adventist Church identity and relevance; without it, Seventh-Day Adventism would’n be the same. However, in recent decades, many have denied or have had a passive attitude towards this vision, both at the level of church and educational institutions (including schools, colleges and universities). This allows us to reflect whether its functions as an educational system is being fulfilled, and how relevant the apocalyptic vision remains in the Adventist Education